Use of condition-based valuation approach to evaluate the maintenance decision of pavement assets: a case study of Yunnan Province in China - Ma, Lei; Cao, Jiang; Pan, Zongjun; Guo, Liming; Zhang, Hai; Ma, Yunqian; Yang, Guang; Wang, Haoyang (Frontiers in Energy Research, 2024)
Pavements are critical components of highway assets, but accurately estimating their value can be challenging due to the lack of connection between valuation and long-term service performance degradation. To address this issue, the replacement cost and condition-based valuation methods were introduced using the Yunnan province highway in China as an example, which divided pavement into four performance states based on service stages. The rationality of maintenance decisions and the impact of preventive maintenance investment on life cycle assessments were also considered. The results indicate that there are issues of irrational allocation of maintenance funds of the highway in Yunnan province, and a higher proportion of preventive maintenance investment is required. Moreover, it is recommended to balance the maintenance funds for bridge and tunnel engineering in the following year, focusing on bridge engineering with a rapid decline in the newness rate. The implementation of preventive maintenance has a positive correlation with the replacement cost and newness rate of the road sections. Through comparison, it was found that the road surface renewal rate in 2019 was lower than that in 2018, and some highway management departments in certain regions need to adjust their preventive maintenance strategies. Overall, the condition-based pavement asset valuation method comprehensively considers each stage of pavement operation and can serve as an effective tool for evaluating pavement asset depreciation. This research finding can promote the sustainable development of road infrastructure.